2012
DOI: 10.1117/12.926326
|View full text |Cite
|
Sign up to set email alerts
|

Development of fast, background-limited transition-edge sensors for the background-limited infrared/sub-mm spectrograph (BLISS) for SPICA

Abstract: We report experimental progress toward demonstrating background-limited arrays of membrane-isolated transition-edge sensors (TESs) for the Background Limited Infrared/Sub-mm Spectrograph (BLISS). BLISS is a space-borne instrument with grating spectrometers for wavelengths λ= 35-435µm and with R=λ/Δλ~500. The goals for BLISS TESs are: noise equivalent power (NEP) = 5×10-20 W/Hz 1/2 and response time τ<30ms. We expect background-limited performance from bilayers TESs with T C =65mK and G=15fW/K. However, such TE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The Very Long Wavelength Grating module is shown in the right panel of Figure 11 as an example of the GM design. SAFARI employs the latest generation of ultrasensitive TES to detect the incoming photons Audley et al, 2016;Suzuki et al, 2016;Goldie et al, 2012;Beyer et al, 2012). TES bolometers fabricated at SRON have already demonstrated the required NEP , as well as the required optical efficiency (Audley et al, 2016).…”
Section: The Safari Detector Grating Modulesmentioning
confidence: 99%
See 1 more Smart Citation
“…The Very Long Wavelength Grating module is shown in the right panel of Figure 11 as an example of the GM design. SAFARI employs the latest generation of ultrasensitive TES to detect the incoming photons Audley et al, 2016;Suzuki et al, 2016;Goldie et al, 2012;Beyer et al, 2012). TES bolometers fabricated at SRON have already demonstrated the required NEP , as well as the required optical efficiency (Audley et al, 2016).…”
Section: The Safari Detector Grating Modulesmentioning
confidence: 99%
“…SAFARI employs the latest generation of ultra-sensitive TES to detect the incoming photons (Khosropanah et al 2016;Audley et al 2016;Suzuki et al 2016;Goldie et al 2012;Beyer et al 2012). TES bolometers fabricated at SRON (Ridder et al 2016) have already demonstrated the required NEP (Khosropanah et al 2016), as well as the required optical efficiency (Audley et al 2016).…”
Section: The Safari Detector Grating Modulesmentioning
confidence: 99%